Competitive Adsorption between Polyethylene Glycol and Acid Brilliant Red on Expanded Graphite - Xiu-Yan Pang; Li-Li Zhang (E-Journal of Chemistry)
Expanded graphite (EG) adsorbent was prepared with graphite as raw materials, potassium permanganate as oxidant, and vitriol as intercalation compound. Polyethylene glycol (PEG) 10000 and Acid brilliant red 3B (ABR) with obvious difference in molecular weights were selected as organic adsorbates, and their adsorption and competitive adsorption thermodynamics and kinetics on EG were investigated. The results are: In both single component system and dual component system, the adsorption and competitive adsorption isotherm of PEG 10000 and ABR on EG are all type I. In dual component system, the existence of another component would decrease the single component adsorbance, which might be caused by the competitive adsorption of these adsorbates for the same adsorbing site on EG. Adsorption and competitive adsorption are spontaneous, and the increase of ionic strength, temperature and expanded volume of the adsorbent would cause the increase of adsorbance. No matter the single component system or the dual component system, the adsorption kinetics models can all be well described with pseudo second-order model. Adsorption rate increases with the increase of temperature. Physical adsorption is the main action between EG with these adsorbates.